Application of Quality Function Deployment (QFD) For Quality Improvement of Suwar Suwir Product - I.B. Suryaningrat (APTA and DTIP FTP UGM, 2017)
Suwar suwir is a traditional food, like a sweet candy, made from sugar and fermented cassava.This product is produced by small and medium agroindustries in Jember. Various and low ofimprovement product are still common problems faced by producers. Evaluation of thisproduct is needed to improve quality of the product. Presently, evaluation of consumerexpectation is never conducted to improve product quality and to answer consumer expectationas well. One of the method used to solve that problem is QFD. Sixty respondents wereinterviewed in this study. Information were collected from many resources such as outletowners, producers, workers, processing operators and marketing staff. We found that 4attributes from consumers were taste, color, aroma and texture which were answered by ninetechnical responses. In term of product performance, based on product comparison analysis,we found that the consumers much more satisfy with suwar suwir produced by Barokah Jayacompare to Primadona and Kartini.Furthermore, the result of QFD analysis showed thatsuwar suwir from Barokah Jaya could achieve the target compare to the competitors. Based onthe results, we concluded that Barokah Jaya could answer consumer’s expectation using itstechnical responses.